Employment effect of citizenship acquisition: Evidence from the Belgian labour market - Sousso Bignandi; Céline Piton (National Bank of Belgium, 2022)
This paper investigates whether citizenship acquisition affects immigrants' employment in Belgium. To do so, we rely on a longitudinal database, over the period 2008-2014, coupling administrative data from the Crossroads Bank for the Social Security (CBSS) and survey data from the Labour Force Surveys (LFS). During this period, citizenship was open to all immigrants who have been legally resident for at least 7 years, without any language or integration requirements. This allows us to study naturalisation in a liberalised context, avoiding part of the selection bias. The econometric analysis has been carried out using panel data fixed effects techniques applied to a programme evaluation model. We find that citizenship acquisition increases immigrants' employment by 7 percentage points after naturalisation. This effect persists even after controlling for endogeneity by exploiting an instrument for naturalisation and thus confirms the existence of citizenship premium in Belgium. Furthermore, the analysis by type of employment shows that citizenship has a positive effect on migrants' entrepreneurship as well as on their probability of finding a better and more stable job. Finally, using cross-section administrative data from the CBSS, covering the entire population, we find that citizenship effect is stronger for individuals with a non-EU origin.
Keywords: J15; J16; J18; J21; 330; Employment; Immigration; citizenship; labour market integration; Belgium